Benzoic acid-2,9-dimethylphenanthroline (1/1) - Arman, H.D.; Kaulgud, T.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The constituents of the title 1:1 co-crystal, C(7)H(6)O(2)center dot C(14)H(12)N(2), are connected into dimeric aggregates by a bifurcated O-H...N hydrogen bond; the hydroxyl-H atom is hydrogen bonded to the two N atoms of the 2,9-dimethylphenanthroline. The hydrogen-bonded residues are almost orthogonal to each other [dihedral angle = 78.56 (7) degrees]. In the crystal packing, the aggregates are assembled into layers in the bc plane by pi...pi interactions [ring centroid...ring centroid distance = 3.5577 (16) A] involving the pyridyl rings, and C-H...pi contacts involving the phenanthroline-H atom and the phenyl ring of the acid.